بلوچی زبان ءِ نبشتہ رہبند: Orthography of Balochi language - Baloch, Hamid Ali (Hanken, 2009)
Balochi is one of the oldest languages in the Iranian region, and spoken in Pakistan, Iran, Afghanistan, Turkmenistan and some other countries of the world but lacks a standard orthographic system. The Baloch linguists have the opinions that 95% is yet awaiting to be resolved. In this paper I will discuss the minute or minor issues converting to the Balochi orthographic system and suggest how to solve these issues.